Hydrogeochemical Modelling of Groundwater at Al-Nile Area, Center of Babylon Governorate, Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study area represented Al-Nile area at Al-Mahaweel district affiliated to Babylon governorate and just (90 km) south of Baghdad governorate and about (20 km) east of Al-Hillah city. This study covered an area about (300 km2) which located between (44°30' & 44°36') E and (32°32' & 32°36') N. The geological setting of the study area characterized by recent sediments of the quaternary period during the Pleistocene and Holocene involves the floodplain deposits. Topographically, the Babylon governorate characterized by a lack of slope with gentle gradient about (22 cm/km) descended from northern and northwestern sides towards the eastern parts and southeastern. The mainly target of this present study is to originate a hydrogeochemical modelling of groundwater in the study area to determine the dissolution and precipitation ratios of the mineral phases along the selected flow paths and also explained the effected ratio of the surface water (Babylon stream) on the groundwater by using the hydrogeochemical mixing technique. Ground and surface water parameters show significant spatial and temporal variations in major and minor element concentrations during the two periods of the study. The mixing process shows us a highly effect of the Babylon stream in the wells (1,7,13 and 21), while show low effected on the wells (3,5,14,19 and 20) with a different contribution